The Future of the U.S. Intercontinental Ballistic Missile Force - Caston, Lauren (RAND, 2014)
The authors assess alternatives for a next-generation intercontinental ballistic missile (ICBM) across a broad set of potential characteristics and situations. They use the current Minuteman III as a baseline to develop a framework to characterize alternative classes of ICBMs, assess the survivability and effectiveness of possible alternatives, and weigh those alternatives against their cost.